Formulasi Hukum Secara Selektif terhadap Pelaku Tindak Pidana Narkoba - Kutono, Edi (Peneliti.net, 2024)
In the era of globalization, many types of crime occur. Violations of norms are becoming more frequent and crimes are increasing, both in type and in patterns becoming more complex. One of them is narcotics and illegal drug crimes, which have now become transnational in nature and are carried out with high modus operandi and sophisticated technology. Drugs can hinder national development with a material-spiritual aspect. Law enforcement officials have an important role in tackling this crime. One of them is a POLRI investigator. Drug trafficking must immediately find a rational solution. This research aims to analyze the implementation of a legal approach in preventing drug abuse and analyzing legal efforts in dealing with and preventing narcotics. This research uses normative juridical research methods, with a statutory and conceptual approach. Data is collected by processing legal materials. Starting with primary legal material, namely an understanding of the legal norms and regulations that support it. Then secondary legal materials are the opinions of legal experts as stated in literature, books or other sources and the last is deductive conclusion drawing. The results of the research show that in statutory regulations there is a diversity of terms for narcotics users which can cause ambiguity in the implementation of law enforcement for law enforcement officers. The principles of restorative justice can be used to resolve narcotics crime cases against addicts, abusers, victims of abusers, narcotics dependants and one-day use narcotics, as regulated in Article 1 of the Joint Regulation of the Chief Justice of the Supreme Court, Minister of Law and Human Rights, Minister of Health, Minister of Social Affairs, Prosecutor Agung, Chief of Police, Head of the National Narcotics Agency Number 01/PB/MA/111/2014, Number 03 of 2014, Number 11 of 2014, Number 03 of 2014 Number Per005/A/JA/03/2014 Number 1 of 2014, Number Perber/01/111/2014/BNN concerning Handling of Narcotics Addicts and Victims of Narcotics Abuse in Rehabilitation Institutions).